KONSUMSI DAN INVESTASI SERTA PERTUMBUHAN EKONOMI SUMATERA BARAT - Shandra, Yosi; Amar, Syamsul; Aimon, Hasdi (Jurnal Kajian Ekonomi, 2012)
ABSTRACT The analysis of aggregate consumption growth, investment and economic growth have been carried out in West Sumatra. The purpose of this study was to clarify   the   effect  of  consumption,      investment,    taxation,   government     spending, consumption   of   the   previous   period,   the   interest   rate   and   disposal   revenue   to GDP in West Sumatra. The study was conducted with descriptive and associative with the use of secondary data in the form of time series, 1994 -2010.  The results on    the   First  Hypothesis     suggests    that  the   development     of  consumption,      the development of investment and the development of government spending together influential     significantly   to   economic     growth.    Partially,    the development        of consumption and the growth of government spending significantly and positively to   affect   economic   growth,   then   the   development   of   a   positive   and   significant effect   of  investment     on  economic     growth.    In  the  Second    Hypothesis     together previous period consumption growth and development of disposibel income and significant    positive   impact    on  the  development      of  consumption.     Partially,   the previous period consumption growth and positive impact on the development of consumption   was   not   significant   and   influential   positive   revenue   development disposibel and significant to the development of consumption. Then on the Third Hypothesis jointly the credit interest rate of investment and economic growth has no   effect   on   the   development   of   significant   investment.   Partially,   credit   interest rates negatively and significant investment toward the development of investment and economic growth has positive influence on   the development and significant investment. The Fourth Hypothesis proved to be influential economic growth on the   development   of   the   tax   was   not   significant   in   West   Sumatra. Government efforts   need   to   be   able   to   continue   to   increase   government   spending   or   reduce taxes by increasing the production of regional output. In addition to government efforts are needed to further improve the quality of human resources by providing education      and   training,   scholarships    and   employment      opportunities     in  labor- intensive   system.   To   overcome   the     problem   of    development     of  investment    the government needs to take expansionary monetary action is by controlling interest rates in order to increase investment development. Key words : consumption, investation, government spending, economic growth